A randomized control trial: insertion of peripherally inserted central catheter (picc) in neonates; mathematical formula versus direct measurement - Jusili, Syamila Huda (2023)
Introduction Peripherally inserted central catheters (PICC) is commonly used in preterm infants. However, many studies have shown a high need for adjustment of their position after insertion. The aim of this study was to test a new method to estimate the ideal catheter depth for cubital PICC insertion in preterm infants. Methods A multi-center randomized, controlled trial was conducted, comparing direct measurement from insertion site to sternal notch (control group) versus a formula based on the length of the infant (intervention group) to estimate the ideal depth of cubital PICC in preterm infants with a birth of less than 1.5kg. The primary outcome was the rate of correctly placed PICCs. Catheter related complications were also monitored. Results There was no difference in baseline characteristics between the intervention group and the control group except for a significant lower birth weight in the intervention group. There was no significant difference in correct placement between the intervention and the control groups (6 out of 25 or 24% vs 10 out of 27 or 37% respectively, p=0.309). There was also no significant difference in complication rates between the two groups. Discussion and conclusion This study did not show benefits of using an alternative formula for estimation of catheter depth for cubital PICC insertion in preterm infants. As in previous studies the rate of correct initial placement was low and there is definitely a need for studies to identify better ways to estimate the depth of PICC insertion for preterm infants.